2016
DOI: 10.3389/fnsys.2016.00036
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury Alters Methionine Metabolism: Implications for Pathophysiology

Abstract: Methionine is an essential proteinogenic amino acid that is obtained from the diet. In addition to its requirement for protein biosynthesis, methionine is metabolized to generate metabolites that play key roles in a number of cellular functions. Metabolism of methionine via the transmethylation pathway generates S-adenosylmethionine (SAM) that serves as the principal methyl (−CH3) donor for DNA and histone methyltransferases (MTs) to regulate epigenetic changes in gene expression. SAM is also required for meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 35 publications
(53 reference statements)
3
56
0
Order By: Relevance
“…On the other hand, a Cys decrease may negatively influence the rate of GSH biosynthesis, thereby contributing to the previously observed decrease in GSH content as a consequence of marked oxidative stress occurring after sTBI [34]. It was recently reported that groups of mTBI and sTBI patients had decreased levels of circulating Met and SAM, much more evident in sTBI than in mTBI patients, thus confirming the existence of an altered methyl-cycle after a traumatic insult [73].…”
mentioning
confidence: 85%
“…On the other hand, a Cys decrease may negatively influence the rate of GSH biosynthesis, thereby contributing to the previously observed decrease in GSH content as a consequence of marked oxidative stress occurring after sTBI [34]. It was recently reported that groups of mTBI and sTBI patients had decreased levels of circulating Met and SAM, much more evident in sTBI than in mTBI patients, thus confirming the existence of an altered methyl-cycle after a traumatic insult [73].…”
mentioning
confidence: 85%
“…Whilst in mild TBI (mTBI), a spontaneous recovery late post-injury was observed, severely injured animals had a permanent decrease of brain GSH up to a week following TBI [56]. In addition, a decrease of GSH in CSF of children who suffered a severe TBI has also been reported [73]. Similarly, lower levels of cysteine and glycine, both fundamental for the GSH biosynthesis, were also demonstrated after mild and severe TBI [74].…”
Section: N-acetyl-cysteinementioning
confidence: 99%
“…Important intermediates include one-carbon metabolites, S-adenosylmethionine (SAM), and several metabolites which are involved in glycolysis and the TCA cycle. SAM is a methyldonor involved in epigenetic changes in gene expression, which is generated from the transmethylation pathway from the metabolism of methionine [46]. Moreover, SAM is involved in the synthesis of phosphatidylcholine.…”
Section: Discussionmentioning
confidence: 99%